Implementation of the Utilization of Green Open Space as an MSME Area: A Case Study at RTH Bunderan Serayu, Madiun City - Purwanto; Erna Winansih; Tonny Suhartono (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The use of Green Open Space (RTH) as a community economic activity is an important strategy for realizing sustainable urban development. This study analyzes public perception using Bunderan Serayu RTH in Madiun City as a Micro, Small, and Medium Enterprises (MSMEs) area and examines its implications for social, economic, environmental, welfare, and regional spatial planning (RTRW) aspects. Using a mixed method, which combines quantitative descriptive analysis through questionnaires and validity-reliability tests (Pearson Product-Moment and Cronbach's Alpha) with a qualitative approach in the form of field observation and regional spatial policy studies. The study found that the public had a positive perception, with an average score of 2.9–3.2 (medium category), of the use of RTH as an MSME area. Economic activities in parks are expected to increase income, strengthen social interactions, and provide psychological benefits that improve people's welfare. However, some respondents highlighted the potential for environmental quality to decline and the need to implement the RTRW policy to regulate zoning and the productive use of public space. This study emphasizes that using RTH can be optimized if supported by adaptive spatial governance, consistent environmental monitoring, inclusive RTRW policy enforcement, and active community participation. These findings are common as a basis for the development of productive green space policies oriented towards public welfare, ecological sustainability, and urban economic empowerment.